Anxiety and its Associated Factors among Frontline Nurses during COVID 19 Pandemic in Selected Hospitals of Kathmandu, Nepal - Ghimire, Prakash; Khadka, Alisha (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: Frontline warier especially, nursing workforce were at potential risk of anxiety during COVID-19 Pandemic that could affect their well-being and work performance. Thus, this study aimed to assess the level of anxiety and its associated factors among frontline nurses working in selected hospital of Kathmandu, Nepal. Methods: A descriptive cross-sectional study was conducted during period of January 2022 to February 2022 in Shree Birendra Hospital and Nepal Police Hospital of Kathmandu, Nepal. Non-probability purposive sampling technique was used to select 101 nurses involving in the direct management of COVID-19 patients. Self-administered method using pretested tool was used to collect the data. Descriptive statistics such as frequency, percentage, mean and standard deviation were used to describe selected variables. Fisher exact test was used to find out the association between anxiety and selected variables. Results: More than half of the nurses (66.3%) had mild to moderate level of anxiety whereas, only 8.9% of nurses had severe anxiety. Age (p=0.005), high risk group in family (0.048), fear of being infected with COVID 19 (p=0.021), and working department (p=<0.001) were found to be statistically significant with anxiety among frontline nurses. Conclusion: Frontline nurses are facing high burden of anxiety during COVID 19 Pandemic. It suggests the need of planning of appropriate coping strategies and interventions to safeguard nurses from the physiological distress and consequences of anxiety, ultimately enabling them to provide quality health services.